Prognostic Factors in First-line Metastatic Renal Cell Carcinoma: How to Improve the Prognostic Ability of the IMDC and MSKCC Score? - Parosanu, Andreea; Stanciu, Miruna; Parlog, Cristina; Orlov, Cristina; Olaru, Mihaela; Popa, Ana Maria; Cotan, Horia; Vrabie, Radu; Iaciu, Cristian; Moldoveanu, Oana; Baston, Catalin; Nitipir, Cornelia (International Journal of Innovative Research in Medical Science, 2022)
Background: The incidence of metastatic renal cell carcinoma has steadily increased. Therefore, it is essential to identify precise biomarkers to predict survival and improve clinical care. Objectives: This study aimed to evaluate potential prognostic factors among patients with mRCC. Methods: We retrospectively analyzed 74 patients with metastatic RCC treated between January 2020 and October 2022. We analyzed which risk factors from the MSKCC and IMDC models more accurate correlated with survival in advanced kidney cancer. Results: We identified that poor performance status, late treatment initiation, anemia, and high LDH are statistically significant prognostic factors for predicting overall survival (OS). Conclusion: Our study raised the possibility of actualization of the classical prognostic factors in metastatic RCC patients.